2020
DOI: 10.1177/2192568220942510
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Lumbar Spinal Stenosis in Patients With Mild Leg Pain Levels Is Associated With Unsatisfactory Outcome

Abstract: Study Design: Prospective register cohort study. Objectives: The indication for surgery in patients with lumbar spinal stenosis (LSS) is considered to be leg pain and neurogenic claudication (NC). Nevertheless, a significant part of patients operated for LSS have mild leg pain levels defined as leg pain ≤minimally important clinical difference (MICD). Information is lacking on how to inform these patients about the probable outcome of surgery. The objective was to report the outcome of surgery for LSS in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A cohort study published in 2020 (2559 patients) reported unsatisfactory outcomes with surgery for LSS in patients with mild leg pain (3 on a 10 point scale) 29. A Cochrane review (five randomised controlled trials, 643 patients) in 2016 reported no clear benefits with surgery compared with non-surgical treatment.…”
Section: Spinal Injectionsmentioning
confidence: 99%
“…A cohort study published in 2020 (2559 patients) reported unsatisfactory outcomes with surgery for LSS in patients with mild leg pain (3 on a 10 point scale) 29. A Cochrane review (five randomised controlled trials, 643 patients) in 2016 reported no clear benefits with surgery compared with non-surgical treatment.…”
Section: Spinal Injectionsmentioning
confidence: 99%
“… 8 Furthermore, the number of surgical procedures performed annually for LSS is on the rise, particularly for minimally invasive surgical approaches. 9 , 10 This trend can be attributed to the increased functional expectations and longer life expectancy of LSS patients.…”
Section: Introductionmentioning
confidence: 99%